British design 2010 : branding & graphic design, packaging design, new media design, interior, retail & event design. - Terrett, Ben, ....- (Amsterdam : Bis, 2009)
British Design 2009/2010 is the fourth edition in a series on British design. The book is divided into five sections: graphic design and branding; packaging design; new media; interior, retail, and event design; and product design. The changes in the design industry in the United Kingdom over the last two years are reflected in this latest edition: many new names now present themselves for the first time, along with many established firms who have experienced the benefits of getting their work out to the international audience of design buyers who using this book.
Keywords: Design, general; Ontwerpen